‘Posledniy’ [Last] vs ‘Krayniy’ [Latest] in Ontological Presentation - E. P. Ivanyan; A. M. Klyushina (Научный диалог)
The question of replacement in the synonymic pair last — latest is considered. Attention is paid to the characteristics of speech stereotypes and types of frames that form substitution in a synonymic pair. The results of a comparative analysis of the heuristics of linguo-creative thinking with the level of speech culture of communicants using catachresis in this pair are presented. The study of replacements in ontological coverage is carried out, taking into account the lexicosemantic, cognitive, generistic, extralinguistic, linguocultural and orthological aspects. The variety of functions of the studied synonymic pair in various types of discourse is described. The relevance of the study is due to the ongoing linguistic fashion to replace the lexeme last with the word latest. The authors dwell on the study of memes related to synonymous replacement, identifying their functions and features. It is shown that when the function of artistic figurative concretization of the depicted is actualized, a mimetic character is manifested in the application of this substitution. The parameters of social reality, which caused the replacements in the synonymous pair of the language fashion of the “first and second wave” are determined. A characteristic of the pragmatic meanings of reflexives in newspaper discourse is proposed in relation to the functions they perform. It is shown that the substitute latest becomes a reflexoid.